Pengaruh Variabel Makroekonomi Inflasi, Harga Emas Dunia dan Hang Seng Index Terhadap Volatilitas Jakarta Islamic Index (JII) Periode Oktober 2011 - Oktober 2014 (Studi Pada Mahasiswi Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis UA - Bestari Kusuma Wardhani; Leo Herlambang (Jurnal Ekonomi Syariah Teori dan Terapan, 2015)
This research attempt to analyze the effect of variabel inflation, gold price and Hang Seng Index to the volatility of Jakarta Islamic Index (JII) in period of October 2011-October 2014.The subject is index of Jakarta Islamic Index in period of October 2011 until October 2014. Typed of data used are the secondary data. This research using quantitatif methods and the analytical methods is multiple linear regression with a significance level of 0.05.The result of this research indicate that the inflation, gold price and Hang Seng index partially provide an insignificant influence on the volatility of Jakarta Islamic Index. However the inflation, gold price and Hang Seng Index simultaneously provide a signification effect on the volatility of Jakarta Islamic Index. Based on the coefficient determination ( ܴଶ) of 0.236 or 23.6% shows that the volatility of Jakarta Islamic Index is influenced by inflation, gold price, and Hang Seng Index.